Animal production systems as a selective environment for antibiotic resistance genes - Ambrožič, Jerneja (Acta agriculturae Slovenica, 2012)
In the last decade antibiotic usage in animal production systems has received a considerable public attention. The use, overuse and misuse of antibiotics provided an excellent environment for the selection and dissemination of antibiotic resistant bacteria and resistance genes across a wide diversity of bacteria, mainly through horizontal gene transfer. Resistance genes move between animal and human bacteria mainly through the food chain. Thus resistance generated in animal production environments could result in the loss of effectiveness of antibiotics used for the treatment of human diseases. The increasing threat of emerging bacterial pathogens resistant to a variety of antibiotics and the economic and human burden have moved the legislators in EU to ban antibiotic usage in animal food production as growth promoters in 2006 and recently proposed further non-binding recommendations toban antibiotics for prophylactic use too. The costs for such actions will presumably be much lower in comparison to the costs of leaving the issue as itis. However, in non EU countries such measures have not been adopted yet. The mechanisms and examples of antibiotic resistance development and dissemination are described, focusing on antibiotics used both in human and veterinary medicine and animal food production.
Keywords: animal husbandry; animal production; živinoreja; antibiotic; antibiotics; antibiotiki; odpornost; resistance genes; food; geni; živila